MATLAB Programming for Simulation of Discrete Dynamic Model - AL Wahab, Adel A. Abed; Nasir, Nihad Mahmoud; Lafta , Alaa Hussien (International Journal of Psychosocial Rehabilitation, 2020)
Here, we considered a discrete-time dynamic model of prey-predator populations’ involved ratio dependent functional response with the goal of disclosing a simulation method using MATLAB. Mathematical model was implemented in MATLAB function that allows simulating the effect of ratio-dependent functional response. The graphical interface shown in this paper is performed using the MATLAB Program.